Effects of aging on water and lubricating oil on the creep behavior of a GFRP matrix composite. (15th May 2017) - de Souza, L.R.; Marques, A.T.; d'Almeida, J.R.M.
Abstract: The creep behavior of an E-glass-polyester matrix composite was evaluated as a function of time of immersion in water and lubricant oil. The effect of the test temperature was also evaluated. It was observed that, after 6 and 14 months of exposure to the aging fluids, the Young's modulus of the composite was reduced by 20% regardless the aging fluid when the test was performed at room temperature. For the tests performed at 60 °C, the effects of immersion in lubricant oil were more severe than those after immersion in water. Variation of the creep behavior due to exposure to water was associated only to physical aging, because the properties' variation was correlated to the amount of absorbed water, decreasing only while the amount of water increased. The test temperature was shown to be the main parameter influencing the creep behavior of the composite. The action of the plasticizing effect of water and reduction of oil viscosity with temperature influenced the results of the steady creep rate when the tests were performed at 60 °C. Micromechanics approach was used to qualitatively explain the experimental results obtained.